The Impact of Financial Distress, Free Cash Flow, Information Asymmetry, and Firm Size on Real Earnings Management - Luhung, Istiqomah Adi; Sari, Shinta Permata (E-Jurnal Akuntansi, 2024)
Companies sometimes experience unfavourable situations, prompting managers to involve themselves in preparing financial reports to engage in earnings management practices. The existence of earnings management practices arises due to the influence of several factors. This research aims to examine the influence of financial distress, free cash flow, information asymmetry, and firm size on real earnings management. The population of this study comprises consumer non-cyclicals companies listed on the Indonesia Stock Exchange from 2020 to 2022. Purposive sampling was utilized as the sampling technique, resulting in a total sample of 64 companies. Multiple linear regression was employed as the analysis technique. The results of this research indicate that financial distress and free cash flow do not have a positive effect on real earnings management. Meanwhile, information asymmetry and firm size have a negative effect on real earnings management. Keywords: Asymmetry Information, Financial Distress, Firm Size, Free Cash Flow, Real Earning Management.